Surgical Therapy of Ovarian Endometrioma: Recurrence and Pregnancy Rates - Maul, Lara V. (Society of Laparoendoscopic Surgeons, 2014)
BACKGROUND AND OBJECTIVES: The study was designed to analyze preoperative clinical and surgical findings at enucleation of ovarian endometrioma with their impact on recurrence and pregnancy rates. METHODS: This is a retrospective study of 550 histologically verified ovarian endometriomas operated on at the Department of Obstetrics and Gynecology, University Hospital Kiel, Germany, between 1995 and 2004. Preoperative data, surgical findings, and postoperative outcomes of 289 cases were analyzed. The average follow-up period was 12.9 years. RESULTS: Ovarian endometriomas recurred in 23.9% of patients. Risk factors identified for recurrence of endometriomas were preoperative pain (P = .013), dysmenorrhea (P = .013), larger cyst size (>8 cm), younger age (<25 years), and preoperative cyst rupture. Factors associated with postoperative dysmenorrhea were younger age <25 years (P < .001), nulliparity (P = .020), and lager cyst size >8 cm (P = .048). Recurrence of pain was influenced by previous surgery of endometrioma (P < .05). Laparoscopy had a higher percentage of symptom-free patients than laparotomy did (49.0% vs 33.3%). Additional postoperative hormonal treatment resulted in a higher spontaneous pregnancy rate (41.4% vs 12.6%; P < .001) but a lower recurrence-free interval rate (70.5% vs 82.6%; P = .050) when compared with surgery only. CONCLUSIONS: We identified preoperative and intraoperative findings associated with higher risk of recurrence of endometrioma, pain, and dysmenorrhea. Patients desiring pregnancy benefited from postoperative hormone treatment, but no favorable results from combined therapy were observed with regard to recurrence rate.